Tendon explant cultures to study the communication between adipose stem cells and native tendon niche - Almeida, Raquel Carvalho Ferreira Costa (2018)
Poor clinical outcomes of tendon repair, together with limited regenerative capacity of the tissue, have triggered the search for alternative regenerative medicine strategies. Human adipose-derived stem cells (hASCs) are being investigated as a promising cell source in contributing for tendon repopulation and reconstruction. However, the mechanisms involved in a potential beneficial effect in tendon regeneration are still to be uncovered. To gain further insights on the bi-directional crosstalk occurring between stem cells and the native tendon niche, it was used an indirect (trans-well) system for co-culturing human tendon explants and hASCs. The maintenance of tissue architecture was studied up to 14 days by histological techniques. The secretion of MMPs was evaluated at day 3. The behavior of hASCs was assessed regarding cell elongation and extracellular matrix (ECM) production. The paracrine communication enhanced collagenolytic activity of MMPs in co-cultures at day 3, in comparison to hASCs alone or tendon explants alone, suggesting that ECM remodeling is triggered early in culture. Moreover, hASCs were spontaneously more elongated in co-cultures and the deposition of collagen type III and tenascin-C by hASCs in co-culture was observed at a lower extent after 7 days, in comparison to hASCs alone, being lately recovered at day 14. Overall, explant co-cultures established herein may constitute a tool for replicating the first steps in tendon healing and help uncovering the bi-directional communication occurring between hASCs and the native tendon niche.